Assessing collaborative planning and the added value of planning support apps in The Netherlands. (February 2022) - Lin, Yanliu; Benneker, Kasper
Although a growing body of literature has examined a variety of planning support systems, few studies have been conducted to understand emerging planning support apps for mobile participation and its impact on collaborative planning. This research develops a conceptual framework for assessing different phases of collaborative planning processes and the added value of planning support apps in stakeholder interaction and management. The case studies include four Dutch regeneration projects, which are ongoing pilot projects of the new Environment and Planning Act and supported by a variety of planning support apps. The data for each case study were collected from multiple sources, including policy documents, interviews with stakeholders and online information. The results show that the apps support to engage many participants, provide real-time communication and facilitate effective interactions between the stakeholder managers and local residents. However, their performance is largely dependent on the user-friendliness of the system. Besides, a good consensus building process in the planning phase has a positive effect on stakeholder management and the performance of the apps in the execution phase.